Immigration to Germany in the seventies and eighties: The role of family reunification - Johannes Velling (Zentrum für Europäische Wirtschaftsforschung (ZEW); ZBW – Leibniz Information Centre for Economics, 1993)
Family reunification was virtually the only way for non-EC-foreigners to immigrate to Germany after the recruitment stop in 1973. However, empirical knowledge on the relative size, the reasons and the accompanying circumstances of family reunification is limited. In the paper, the reunification of foreign families whose head lives in Germany is considered using data from the German Socio-Economic Panel 1984-1989. Family reunification is identified in two different ways. Whereas the retrospective approach looks backward from 1985 using information about the year of migration, the year of marriage, and the position in the household, the approach on a year-to-year base uses the panel design of the SOEP identifying family reunification by the reason of movement into the household and out of the household, respectively. The relative size of family reunification in proportion to total immigration as well as the linkage to the business cycle fluctuations is determined. Family reunification is analyzed within the framework of a discrete hazard rate model. The relative importance of several factors reflecting the economic and social situation of the family's head on the decision to have spouse and children come to Germany is examined. It turns out that besides nation-specific differences, years since migration, years since marriage, the degree of social integration in Germany, income and unemployment status by the individual and in the economy, as well as the family background are important determinants for the decision to reunite the family.
Keywords: 330; Internationale Arbeitsmobilität; Internationale Wanderung; Alleinerziehende; Deutschland